THE EFFECT OF THE NUMBERED HEAD TOGETHER LEARNING MODEL ON THE MATHEMATICS LEARNING OUTCOMES OF GRADE IV STUDENTS AT UPTD SD NEGERI 124394 PEMATANGSIANTAR - Yensiska R Siburian; Hetdy Sitio; Yanti Arasi Sidabutar (RADJA PUBLIKA, 2025)
The purpose of this study was to determine the Effect of the Numbered Head Together Learning Model on the Mathematics Learning Outcomes of Fourth Grade Students at the UPTD of State Elementary School 124394 Pematangsiantar. This study uses a quantitative research type using an experimental method (pre-experimental design). Data analysis is quantitative/statistical, with the aim of testing the established hypothesis. The study population was 23 students in the UPTD of State Elementary School 124394 Pematangsiantar located on Jl Tongkol Pematangsiantar. The sample in this study was taken from one class used as a One Group Pretest-Posttest class so that the sample in this study was all fourth grade students of UPTD of State Elementary School 124394 Pematangsiantar. The data analysis technique used was the N-Gain test and Hypothesis Test. The results of the study obtained were an increase in students' creative thinking abilities, namely with an average posttest of 83.91 while the pretest was 41.95. This can be seen from the results of the N-Gain test, there is an influence of the Numbered Head Together Learning Model on the Mathematics Learning Outcomes of Class IV Students at the UPTD of SD Negeri 124394 Pematangsiantar.